PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR ENERGY DAN BASIC MATERIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2021–2023 - Muhammad Azril Fakhrizal Anshari; Wiwiek Prihandini (JURNAL ILMIAH EDUNOMIKA, 2024)
This reseacrh aims is to examine the impact of environmental, social, governance (ESG) disclosure and financial performance consisting of profitability ratios, liquidity ratios, solvency ratios and activity ratios on firm value which is proxied by Tobin’s Q. The data used in this study are secondary data, including financial statements, annual reports, and sustainability reports published by the company. The sample of this reseacrh consisted of 105 observations selected using purposive sampling from energy and basic material sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. This research is a quantitative study using a multiple linear regression model with fixed effect (FEM). The data was analyzed using eviews 12. The result of this researchs show that financial performance proxied by total asset turnover ratio has a positive and significant influence on firm value. Meanwhile, environmental, social, governance (ESG) disclosure and financial performance proxied by the return on equity ratio, current ratio and debt to equity ratio has no significant influence on firm value. Keyword: ESG Disclosure; Financial Performance; Firm Value